Poetry in handcrafting with elements of nature in teacher training for early Childhood Education (Revista Apotheke, 2025)
This experience report is part of a pedagogical proposal for the course “Cultural Activities III - Children and Nature: Pedagogical Experiments,” offered in the Pedagogy program at Fluminense Federal University (UFF) in Niterói. We seek to reflect on the elements of nature that are part of the immediate world and their pedagogical potential as replacements for materials used in early childhood education, such as ethylene vinyl acetate (E.V.A), glitter, plastics, A4 paper, and the environmental impacts of their disposal. Invited to walk around the university campus, we collected twigs, coconuts, pods, leaves, flowers, seeds, and insect shells, among other things, which would be part of an artistic composition using clay. This exercise broadened our familiar perspectives, making them curious, cultivating new ways of seeing, feeling, and interacting with/in the world, sparking imagination and creativity. Immersed in the collection, we questioned how we experience nature in the daily routine of Early Childhood Education and the prevalence of activities focused on commemorative dates. We cultivated the poetry of handmade work and sensory experiences in teacher training, highlighting the appreciation of an aesthetic of ordinariness (Barros, 2010), made of fragments, small pieces of the world, unimportant people, and disobjects, revisited and reinvented. Through aesthetic awareness of the elements of nature and clay, pedagogical practices aligned with legal documents and environmentally sustainable are defended, reinforcing the relevance of offering teachers in training different pedagogical and artistic experiences that expand their repertoire and knowledge of the world.
Keywords: early childhood education; clay; aesthetic training; sustainable practices; environment